Design-build - Thomas, Andrew (Chichester, West Sussex ; Hoboken, NJ : Wiley-Academy, 2006)
Design and Build is the latest in the Architecture in Practice series, and one of the few books on the market that looks directly at Design and Build. Design and Build has become the dominant way of procuring a building, and it is now used from the smallest commercial extension up to the largest privately financed building.
Introduction. Mailbox, Birmingham. Procurement Route (The Client Choices). Kingsmead Citiplex, Bath. 'Design-Build'. The Contract Documents. Tendering. The Project. Consultant Appointment. The Construction Contract. The Consultant's Role. The Project Team (Who's Who). Choosing the Correct Procurement. PFI. Case Studies. Design Management. Value Engineering. The Way Forward. Notes. Photocredits. Terminology. Bibliography. General Information.
Includes bibliographical references (pages 256).
Keywords: Architectural practice; Architectural design